Islamic Intellectual Movement Patterns - M. Ikhsan Nawawi (Jurnal Ilmiah Edukatif, 2023)
The occurrence of cultural contact between the West and East awakens Muslims, depending on the problems that arise and are faced by the intellects in a country, so that the forms of scientific movement patterns that can not be respected from social, economic, and social backgrounds. politics and religion that surrounds it. Its role globally is recorded neatly in gold ink in many pages of history. Under Islamic control, his views on ideological independence and his attitude towards the rules of life were very clear, which was marked by syumuliah (universality) because he was indeed handed down as a living system. The long journey of intellectuals and works that have been carved by Indonesian scholars is an invaluable source of information in exploring their thinking models when facing the development of the situation and the demands of their times. It seems interesting to examine the implications of their thinking on the dynamics of contemporary Islamic thought and modernization. Most of them have created educational models that are unique and interesting and remain relevant at all times. How do the scholars who have specialized themselves to study and teach their knowledge, have a high enthusiasm to continue the legacy of the Prophets to all Muslims without knowing the territorial boundaries. The love of knowledge, the struggle to gain knowledge, and their preservation of knowledge are exemplary for Muslims today. On knowledge is also able to deliver to become a great figure throughout the ages who leave traces (atsar) that are good for the next generation. This paper seeks to explore the patterns used by Muslim intellectuals in the history of Islam of the various movements used in facing challenges.